Multi-technique characterization of the precipitates in thermally aged and neutron irradiated Fe-Cu and Fe-Cu-Mn model alloys: Atom probe tomography reconstruction implications. (March 2018) - Shu, Shipeng; Wirth, Brian D.; Wells, Peter B.; Morgan, Dane D.; Odette, G. Robert
Abstract: Cu precipitation in Fe is technologically and scientifically important. Atom probe tomography (APT) often reports high Fe in copper rich precipitates (CRPs). Some argue that this is an APT artifact. Here, Fe-0.80 at. % Cu (Fe-Cu) and Fe-0.78 at. % Cu-1.05 at.% Mn (Fe-Cu-Mn) alloys were characterized by several microanalytical techniques, following thermal aging and neutron irradiation that produced a high density of nanoscale CRPs. The CRP number densities, mole fractions and sizes characterized by different techniques are reasonably consistent, but not the compositions in the case of APT. A new small-angle neutron scattering method was used, involving measuring the temperature dependence of magnetic scattering (T-SANS), which proved that the CRPs are non-magnetic at ambient temperature. Nuclear scattering mass balance constraints show that CRPs do not contain a significant amount of Fe. Positron annihilation spectroscopy and SANS magnetic-to-nuclear scattering ratio measurements are also consistent with very small amounts, if any, of Fe in the CRPs. Graphical abstract: Image 1